Innovation through Joint Ventures. Implications and Role of the Top Management Team (2019)
Although equity-based arrangements, particularly Joint Ventures, are more effective than the contractual ones when trying to have access to knowledge needed for innovation, research on the factors on how to successfully achieve the development and implementation of this strategy is scarce and scattered. From the Upper Echelon Theory, the objective of this work is to develop a review and integration of the literature about shared control Joint Ventures, top management teams and innovation and to propose a framework of relationships. The role and implications of the top management team in carrying out a Joint Venture created to innovate is analyzed in this article, having as a conclusion that the diversity of the TMT (top management team) can positively or negatively influence the results of such innovation. The directive nature of their work in relation to the parent companies may hinder the achievement of the objectives for which they were created. Other factors that may help correct the negative implications about innovation, created by the team composition and the characteristics of their work, are also considered.